Educational Robotics Practices and Progress in Brazil and Peru - Gonçalves, Luiz Marcos Garcia; Garcia, Luciane Terra dos Santos; Patiño-Escarcina, Raquel Esperanza; Barrios-Aranibar, Dennis (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
Educational Robotics (ER) has emerged as a dy-namic tool to enhance learning in STEAM (Science, Technology, Engineering, Arts, and Mathematics) education, fostering com-petencies, creativity, and problem-solving skills. Latin America, particularly Brazil and Peru, has seen a growing interest in incorporating ER into school curricula. However, the scale and form of implementation differ significantly between these two countries, especially when looking at public and private educational institutions. This article presents a joint analysis of ER policies, practices, and results in public and private schools in Brazil and Peru. Through examining national initiatives, pedagogical methodologies, and teacher training programs, we elucidate the advancements and challenges in integrating ER into educational systems of both countries. We highlight the challenges, innovations, and educational impacts observed in both nations and provide recommendations for equitable and effective expansion.